Enzyme activity and morphological changes in corn hybrids inoculated with Azospirillum brasilense via seed treatment and leaf - T. M. Müller; L. A. Tabaldi; G. M. Fipke; V. S. Cunha; L. P. Ribeiro; T. N. Martin (Brazilian Journal of Biology)
Abstract Plants possess a defense system for minimizing the stresses caused by nutrient deficiencies. The objective of this study was to evaluate the enzymatic and morphological changes in corn hybrids inoculated with Azospirillum brasilense. The experiment was set up in a completely randomized design comprising six corn hybrids inoculated with A. brasilense via a seed treatment and a leaf application during the V2 stage. The following hybrids were used: AG9045, AG8025, AG2040, Feroz, BG7051, and BG7060. The biochemical variables were lipid peroxidation, the activity of the superoxide dismutase, guaiacol peroxidase, and nitrate reductase (NR) enzymes and the level of total chlorophyll and carotenoids. Were analyzed in the shoots and in the roots, along with the following morphological variables: the leaf area (LA); shoot dry weight; and the length, projected area, surface area, diameter, volume, number of branches, and dry weight of roots. For the shoots, the greatest activity of SOD occurred in BG7060 when A. brasilense was applied during the V2 stage, which prevented damage to the membrane lipids. The NR activity of the shoots was greater for the control than for the bacterial treatments, with the presence of the bacterium reducing the activity of this enzyme. The bacterium showed efficiency for the variables root projected area and surface area in the AG8025 and AG2040 hybrids. Thus, the hybrids behave differently in the presence of the bacterium, which positively affects the activity of the antioxidant enzymes and increases the root system and LA of the plants.